How Does Intellectual Capital Affect Micro, Small, and Medium Business Resilience During the Covid-19 Pandemic? - Irena Paramita Pramono; Nunung Nurhayati; Roziyana binti Jafri; Laila Sugiarta (Research Synergy Foundation, 2023)
Many previous studies examined the relationship between Intellectual Capital (IC) and a firm’s performance, whereas most of the time, IC has been shown to affect a firm’s performance positively. However, two years during the COVID-19 pandemic differs from the ordinary years. There was a massive change in people's economic activities. Restrictions on people's movement and mobility are needed to prevent the spread of the COVID-19 outbreak. Apart from causing crises in the health sector, this pandemic also causes concerns in the social and economic sectors, including MSMEs. Therefore, this research was conducted to understand the effect of IC, including Human Capital (HC), Structural Capital (SC), and Relational Capital (RC), on MSME resilience during the pandemic period. This information is essential to formulate the best support for MSMEs in the IC context. This research is quantitative research using Ordinary Least Square (OLS). Data were collected by distributing questionnaires to 174 MSMEs in Bandung using the random sampling technique. The type of data used is cross-section data. This study found that HC and RC positively affect MSME resiliency during the pandemic, meanwhile, SC does not. This study suggests that the most appropriate form of support for MSMEs in times of crisis is to provide education and knowledge sharing which can expand the skills and knowledge of MSME businesspeople. And in addition, it is also important to support MSMEs in developing their relationships with various parties to maintain their business during the pandemic.